Electrochemical characterisation of Co@Co(OH)(2) core-shell nanoparticles and their aggregation in solution - Xie, R-C; Batchelor-McAuley, C; Rauwel, E; Rauwel, P; Compton, RG (Wiley, 2020)
Core-shell Co@Co(OH)2 nanoparticles are characterised electrochemically with particular focus on the thin shell of cobalt (II) hydroxide which stabilises the metallic cobalt core against further oxidation in the presence of air. Voltammetric characterisation allows insights into the nature of the shell so both complementing and providing information unavailable using electron microscopy and X-ray diffraction. Moreover, the electrode reactions, occurring at particle ensembles, of the further oxidation of surface Co(OH)2 to CoOOH under alkaline conditions are further evidenced at the single particle level using electrochemical particle-electrode impacts (or ‘nano-impacts’). On this basis, the large extent of particle agglomeration/aggregation of Co@Co(OH)2 nanoparticles while suspended in the solutions is inferred.